The illustrated encyclopedia of the elements : the powers, uses, and histories of every atom in the universe - Congdon, Lisa (Chronicle Books, 2021)
Presents an illustrated look at the elements of the periodic table. Provides information on atoms, compounds, and states of matter, as well as the discovery, uses, and special properties of each element. Includes infographics, profiles of notable scientists, a glossary, and trivia.